2019
DOI: 10.1002/ece3.5167
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and possible origins of weedy rice found in California

Abstract: Control of weeds in cultivated crops is a pivotal component in successful crop production allowing higher yield and higher quality. In rice‐growing regions worldwide, weedy rice (Oryza sativa f. spontanea Rosh.) is a weed related to cultivated rice which infests rice fields. With populations across the globe evolving a suite of phenotypic traits characteristic of weeds and of cultivated rice, varying hypotheses exist on the origin of weedy rice. Here, we investigated the genetic diversity and possible origin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
0
27
0
2
Order By: Relevance
“…Today, it is generally accepted that weedy rice has originated independently in different geographical areas of the world. Both exoferality and endoferality have been shown to contribute to the establishment of weedy rice populations (De Leon et al, 2019;Huang et al, 2017;Li, Li, Jia, Caicedo, & Olsen, 2017;Reagon et al, 2010;Song, Chuah, Tam, & Olsen, 2014;Vigueira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Today, it is generally accepted that weedy rice has originated independently in different geographical areas of the world. Both exoferality and endoferality have been shown to contribute to the establishment of weedy rice populations (De Leon et al, 2019;Huang et al, 2017;Li, Li, Jia, Caicedo, & Olsen, 2017;Reagon et al, 2010;Song, Chuah, Tam, & Olsen, 2014;Vigueira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These biotypes are distinguishable from each other by phenotypic differences, including presence and length of awns, hull color, and grain size (Table 1). They are also genetically distinct and have separate origins from diverse rice ancestors (De Leon et al 2019). Although the effects of weedy rice competition on cultivated rice yield has been studied for other locations and weedy rice biotypes, the effects of competition on growth and yield of California rice cultivars due to local weedy rice biotypes have not been previously investigated, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Accessions were obtained from growers' rice fields in Glenn, Colusa, Butte, Yuba, and Sutter counties in the northern Sacramento Valley region of California. The five biotypes of California weedy rice used in this study are characterized by genetic differences (De Leon et al 2019), which correspond with observed differences in hull color, presence of awns, plant stature, and grain size (Table 2). To enable comparison with other weedy and wild rice, we included 5 weedy rice accessions from the southern United States (Arkansas, Mississippi, and Texas) and 3 wild rice species.…”
Section: Plant Materialsmentioning
confidence: 52%
“…Some studies of southern U.S. weedy rice have indicated that weedy rice biotypes similar in height to cultivated rice may be hybrids with local cultivars (Burgos et al 2014;Gealy et al 2003;Singh et al 2017b), although there are exceptions (Gealy et al 2012). Type 4 weedy rice is likely not a hybrid with cultivated rice, as it is otherwise not phenotypically similar to California rice varieties ( Figure 1A) and is genetically distant from them (De Leon et al 2019). Weedy rice biotypes from the southern United States have large variation in heading or flowering date, similar to California biotypes (Kanapeckas et al 2017;Shivrain et al 2010;Thurber et al 2013).…”
Section: Factor Loadingsmentioning
confidence: 99%
See 1 more Smart Citation